2021
DOI: 10.1021/acsami.1c14385
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Drug Delivery System from Macrocycle-Based Self-Assembled Amphiphiles for Effective Tumor Therapy

Abstract: Intelligent drug delivery systems (DDSs) that can improve therapeutic outcomes of antitumor agents and decrease their side effects are urgently needed to satisfy special requirements of treatment of malignant tumors in clinics. Here, the fabrication of supramolecular self-assembled amphiphiles based on the host−guest recognition between a cationic water-soluble pillar[6]arene (WP6A) host and a sodium decanesulfonate guest (G) is reported. The chemotherapeutic agent doxorubicin hydrochloride (DOX) can be encaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…In addition to the stimuli from microenvironment, we can also use external stimuli, such as light, ultrasound, and magnetic fields, to obtain stimuli responsiveness. According to the source of the stimuli and the mode of action, stimuli‐responsive polymersome‐based delivery systems can be divided into: (1) chemical stimuli, including pH (Du, Chen, et al, 2012b; Johnson et al, 2015; Wang, Yang, et al, 2016c), redox (Bej et al, 2020; Curcio et al, 2015; Hu et al, 2018; Karandish, Mamnoon, et al, 2018b; Laskar et al, 2019; Wang et al, 2014), reactive oxygen species (Zhou, Feng, et al, 2017b), potassium ion (You et al, 2017); (2) physical stimuli, such as temperature (Kozlovskaya et al, 2019; Liu, Kozlovskaya, et al, 2015a), light (Park et al, 2018), X‐ray (Zhou, Chan, et al, 2018b), magnetic field (Oliveira et al, 2013), ultrasound (Wang, Yin, et al, 2018c; Wei, Sun, et al, 2020a); (3) biological stimuli, such as enzyme (Pramod et al, 2015), adenosine triphosphate (ATP) (Chen et al, 2021). Among which, pH‐ and redox‐ responsive polymersomes were mostly reported.…”
Section: Intelligent Design Of Polymersomes For Improved Cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the stimuli from microenvironment, we can also use external stimuli, such as light, ultrasound, and magnetic fields, to obtain stimuli responsiveness. According to the source of the stimuli and the mode of action, stimuli‐responsive polymersome‐based delivery systems can be divided into: (1) chemical stimuli, including pH (Du, Chen, et al, 2012b; Johnson et al, 2015; Wang, Yang, et al, 2016c), redox (Bej et al, 2020; Curcio et al, 2015; Hu et al, 2018; Karandish, Mamnoon, et al, 2018b; Laskar et al, 2019; Wang et al, 2014), reactive oxygen species (Zhou, Feng, et al, 2017b), potassium ion (You et al, 2017); (2) physical stimuli, such as temperature (Kozlovskaya et al, 2019; Liu, Kozlovskaya, et al, 2015a), light (Park et al, 2018), X‐ray (Zhou, Chan, et al, 2018b), magnetic field (Oliveira et al, 2013), ultrasound (Wang, Yin, et al, 2018c; Wei, Sun, et al, 2020a); (3) biological stimuli, such as enzyme (Pramod et al, 2015), adenosine triphosphate (ATP) (Chen et al, 2021). Among which, pH‐ and redox‐ responsive polymersomes were mostly reported.…”
Section: Intelligent Design Of Polymersomes For Improved Cancer Therapymentioning
confidence: 99%
“…(3) biological stimuli, such as enzyme (Pramod et al, 2015), adenosine triphosphate (ATP) (Chen et al, 2021). Among which, pH-and redox-responsive polymersomes were mostly reported.…”
Section: Stimuli-responsiveness Of Polymersome-based Delivery Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, supramolecular chemotherapy has received considerable attention by utilizing a supramolecular strategy to decrease the cytotoxicity of anticancer drugs to normal cells while preserving their cytotoxicity against cancer cells [ 11 ]. Supramolecular systems derived from macrocycles [ 12 13 ], such as calix[ n ]arenes (CXs), cyclodextrins (CDs), cucurbiturils (CBs), and pillararenes, are of particular interest because they can act as vehicles for anticancer drugs by either self-assembling into nanocarriers [ 14 16 ] or forming host–guest complexes with anticancer drugs [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the host–guest complexation of CP6A with 20 naturally occurring amino acids was investigated using an indicator displacement assay. 42–44 A competitive fluorescence titration was carried out to qualitatively determine their association constants ( K a ) in phosphate buffer solution (PBS) at pH 7.4. Previous work has reported that CP6A could effectively quench fluorescence of acridine orange (AO) with a suitable binding affinity.…”
mentioning
confidence: 99%